An exploration of the impact of younger-onset dementia on employment - Evans, David (Dementia (London, England), 2019)
This study explored the emergence of dementia in people who were still working. A qualitative life course approach was used to describe the experience from the onset of dementia-related symptoms to the time when the person left the workforce. The emergence of dementia at work for the participants in this study took the form of a slow transition that initially was not noticed by co-workers. It brought about subtle changes as the person became forgetful, disorganised, made mistakes and was slower. Over time the person’s job performance continued to deteriorate and others at the workplace started to realise that there was a problem. Some were seen to be poor workers and so experienced difficulties with supervisors and co-workers. Others encountered difficulties managing changing relationships at work and negotiating the complex world of the workplace. Few were able to continue working beyond their diagnosis, and several raised concerns about the lack of opportunities for people who develop dementia while still employed. Given the greater participation of older people in the workforce, findings highlight the importance of identifying and supporting workers with declining cognitive function.